Tricks with tetramers: how to get the most from multimeric peptide–MHC - Wooldridge, Linda (Blackwell Science Inc, 2009)
The development of fluorochrome-conjugated peptide–major histocompatibility complex (pMHC) multimers in conjunction with continuing advances in flow cytometry has transformed the study of antigen-specific T cells by enabling their visualization, enumeration, phenotypic characterization and isolation from ex vivo samples. Here, we bring together and discuss some of the ‘tricks’ that can be used to get the most out of pMHC multimers. These include: (1) simple procedures that can substantially enhance the staining intensity of cognate T cells with pMHC multimers; (2) the use of pMHC multimers to stain T cells with very-low-affinity T-cell receptor (TCR)/pMHC interactions, such as those that typically predominate in tumour-specific responses; and (3) the physical grading and clonotypic dissection of antigen-specific T cells based on the affinity of their cognate TCR using mutant pMHC multimers in conjunction with new approaches to the molecular analysis of TCR gene expression. We also examine how soluble pMHC can be used to examine T-cell activation, manipulate T-cell responses and study allogeneic and superantigen interactions with TCRs. Finally, we discuss the problems that arise with pMHC class II (pMHCII) multimers because of the low affinity of TCR/pMHCII interactions and lack of ‘coreceptor help’.